The ecological world view - Krebs, Charles J. (CSIRO Publishing ; CABI, 2008)
This new textbook fills an important niche by offering a lively overview of the principles of ecology for a broad range of college-level science and biology courses. Written for those who need to understand key ecological concepts but may specialise in other fields, it is filled with many vivid examples of topical issues and current events.